Performance of grass-legume pastures under coconuts in Indonesia - Mullen, BF; Rika, IK; Kaligis, DA; Stür, Werner W. (Cambridge University Press, 1997)
A series of grazed and cut experiments were conducted in Bali and North Sulawesi, Indonesia, between 1992 and 1994, to evaluate a range of selected forages for both intensive and extensive ruminant production under mature, tall coconuts. Yield, botanical composition and persistence of grass legume mixtures were assessed under regular grazing and cutting regimes. In North Sulawesi, total dry matter yields of most grass legume treatments were relatively stable over the two-year period but yields of legume components within treatments declined sharply. In Bali, the grazed plots maintained stable yield and legume components over the experimental period but yield and legume components of cut plots declined sharply. Paspalum malacophyllum and Setaria sphacelata cv. Splenda were productive and persistent grasses and formed weed-free swards but did not combine well with prostrate legumes. The erect growth habit of these grasses may limit their suitability in coconut production systems by impeding nut collection. The prostrate species Brachiaria humidicola and Stenotaphrum secundatum were slightly less productive but equally weed-free and persistent, and established rapidly from cuttings. S. secundatum also formed stable associations with prostrate legumes under grazing. Arachis pintoi cv. Amarillo and A. glabrata CPI 93483 were the most persistent of a range of prostrate legumes. The tree legume, Calliandra calothyrsus, showed promise as a productive cut-and-carry species.